Voice biomarkers in middle and later adulthood as predictors of cognitive changes - Mahon, Elizabeth; Lachman, Margie E. (Frontiers in Psychology, 2024)
Background: Prosody voice measures, especially jitter and shimmer, have been associated with cognitive impairment and hold potential as early indicators of risk for cognitive decline. Prior research suggests that voice measures assessed concurrently with longitudinal cognitive outcomes is associated with 10-year cognitive declines in middle-age and older adults from Midlife in the U.S. (MIDUS) study. Results: Using a subsample from the same study, we expanded previous research to examine voice measures that were 1) collected 8 years before cognitive outcomes, 2) derived from narrative speech in logical memory tests instead of word list recall tests, and 3) independent of the cognitive outcomes. Multilevel analyses controlled for covariates of age, sex, education, neurological conditions, depressive symptoms, and chronic conditions. The results indicated that higher jitter and lower shimmer predicted greater 10-year declines in episodic memory and working memory. Conclusions: These findings extend previous findings by highlighting prosody voice measures assessed 8 years earlier as predictors of subsequent cognitive declines over a decade.